Paradoxes of Teaching Thailand’s History in Chiang Mai Marginal Schools - Mangkhang, Charin; Srathongchun , Kittiphat; Nuansawan, Pimpa (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
This article aims to provide a critical reflection on the teaching of Thai history in marginalized schools in Chiang Mai by examining structural problems in current practices, analyzing curriculum limitations, and proposing context-appropriate learning approaches. The research methodology combines documentary analysis with a field study of history classrooms conducted in three schools (three classrooms) located in the marginalized areas of Chiang Mai. The study also applies Taba’s curriculum framework and posthumanist educational theory to evaluate the suitability of learning processes. The findings reveal that the Thai history curriculum emphasizes a state-centered identity while neglecting the integration of local histories of marginalized groups. This leads to learners’ alienation and lack of diverse perspectives. In addition, rote memorization and standardized testing hinder the development of learners’ analytical thinking. Therefore, this article proposes alternative learning strategies that incorporate modern technology, such as Virtual Reality (VR), local learning resources, and experiential learning to enhance relevance, promote inclusive historical understanding, and reduce educational inequalities.